2022
DOI: 10.7146/hjlcb.vi62.128116
|View full text |Cite
|
Sign up to set email alerts
|

Reading English Texts through Telegram App: Indonesian Vocational Students’ Perceptions

Abstract: This study investigates how the students perceive the use of Telegram on their reading comprehension. For this purpose, 104 students in an Indonesian vocational school who are from various majors are selected to fulfil an online questionnaire about Telegram acceptance for learning English. Then, its result is compared to the score of students’ reading comprehension. For its validity of reading comprehension achievement, this study employs construct validity of the reading text that the English teacher gives. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Additionally, Telegram enables autonomous learning, fosters a friendly and welcoming atmosphere, and facilitates connectivity between students and teachers. These findings align with those of Suci et al (2022), who concluded in the study that the integration of the media in the class creates good chances for enjoyable experiences in learning the language and promotes an interactive classroom environment. In conclusion, incorporating Telegram as a teaching application offers an alternative approach to generating student interest and creating a comfortable atmosphere during English instruction.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Additionally, Telegram enables autonomous learning, fosters a friendly and welcoming atmosphere, and facilitates connectivity between students and teachers. These findings align with those of Suci et al (2022), who concluded in the study that the integration of the media in the class creates good chances for enjoyable experiences in learning the language and promotes an interactive classroom environment. In conclusion, incorporating Telegram as a teaching application offers an alternative approach to generating student interest and creating a comfortable atmosphere during English instruction.…”
Section: Discussionsupporting
confidence: 89%
“…The availability of learning resources can significantly impact students' reading scores, particularly their scanning and skimming scores. Anggraini & Cahyono (2020) and Suci et al (2022) claimed that technological tools provide intrinsic incentives for learners in terms of reading comprehension, which can positively influence their performance, especially in reading. The motivating aspects of new technological tools and environments were evident in this research, as most learners willingly participated in instructional activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Socrative and Moodle in this research do not provide any features that can attract the students' learning interactions. Therefore, reading comprehension may be influenced not only by the use of technology (Suci et al, 2022).…”
Section: Discussionmentioning
confidence: 99%